Saturation mutagenesis of selected residues of the α‐peptide of the lantibiotic lacticin 3147 yields a derivative with enhanced antimicrobial activity. Issue 5 (25th February 2013) - Field, Des; Molloy, Evelyn M.; Iancu, Catalin; Draper, Lorraine A.; O' Connor, Paula M.; Cotter, Paul D.; Hill, Colin; Ross, R. Paul
Summary The lantibiotic lacticin 3147 consists of two ribosomally synthesized and post‐translationally modified antimicrobial peptides, Ltnα and Ltnβ, which act synergistically against a wide range of Gram‐positive microorganisms. We performed saturation mutagenesis of specific residues of Ltnα to determine their functional importance. The results establish that Ltnα is more tolerant to change than previously suggested by alanine scanning mutagenesis. One substitution, LtnαH23S, was identified which improved the specific activity of lacticin 3147 against one pathogenic strain, Staphylococcus aureus NCDO1499. This represents the first occasion upon which the activity of a two peptide lantibiotic has been enhanced through bioengineering.